This Was Not Our War : Bosnian Women Reclaiming the Peace - Hunt, Swanee; Project Muse. (Durham : Duke University Press, 2004)
Combines Bosnian women's personal testimony about the recent war and its aftermath with Ambassador Hunt's analysis of the U.S. government's appproach to the conflict.
Introduction -- pt. 1. Madness -- Hell breaks loose -- Love in the crucible -- Reasons for the war -- The lie of intractable hatreds -- pt. 2. To heal history -- Challenges -- Women transforming -- The road to reconciliation -- Epilogue: The courage to hope -- Profiles -- Closing thoughts.
English.
Description based on print version record.
Keywords: Hunt, Swanee; Hunt, Swanee -- Voyages -- Bosnie-Herzegovine.; Hunt, Swanee -- Travel -- Bosnia and Herzegovina; Frau; Protestbewegung; Women; Travel; Protest movements; Politics and government; HISTORY -- Europe -- General; Society and social sciences Society and social sciences; Society and culture: general; Social groups; Gender studies, gender groups; Guerre dans l'ex-Yougoslavie, 1991-1995 -- Contestation; Guerre dans l'ex-Yougoslavie, 1991-1995 -- Femmes -- Bosnie-Herzegovine.; Yugoslav War, 1991-1995 -- Protest movements; Yugoslav War, 1991-1995 -- Women -- Bosnia and Herzegovina; Bosnien-Herzegowina -- Bürgerkrieg.; Bosnia and Herzegovina; Bosnie-Herzegovine -- Politique et gouvernement -- 1992-; Bosnia and Herzegovina -- Politics and government -- 1992-; Electronic books